Manufacturing Strategies for Solid Electrolyte in Batteries - Chen, Annan; Qu, Conghang; Shi, Yusheng; Shi, Feifei (Frontiers in Energy Research, 2020)
Throughout the development of battery technologies in recent years, the solid-state electrolyte (SSE) has demonstrated outstanding advantages in tackling the safety shortcomings of traditional batteries while meeting high demands on electrochemical performances. The traditional manufacturing strategies can achieve the fabrication of batteries with simple forms (coin, cylindrical, and pouch), but encounter limitations in preparing complex-shaped or micro/nanoscaled batteries especially for inorganic solid electrolytes (ISEs). The advancement in novel manufacturing techniques like 3D printing has enabled the assembly of different solid electrolytes (polymeric, inorganic, and composites) in a more complex geometric configuration. However, there is a huge gap between the capabilities of the current 3D printing techniques and the requirements for battery production. In this review, we compare the traditional manufacturing to several novel 3D printing techniques, highlighting the potential of 3D printing in the SSE manufacturing. The latest SSE manufacturing progress in the group of direct-writing (DW) based or lithography-based printing technologies are summarized separately from the perspectives of feedstock selection, build envelope, printing resolution, and application (nano-scaled, flexible, and large-scale battery grids). Throughout the discussion, some challenges associated with manufacturing SSEs via 3D printing such as air/moisture sensitivity of samples, printing resolution, scale-up capability, and long-term sintering for ISEs have been put forward. This review aims to bridge the gap between 3D printing techniques and battery requirements by analyzing the existing limitation in SSE manufacturing and point out future needs.